Error Analysis Of Students’ Independent Writing (A Descriptive Study At The English Department Of STKIP PGRI Nganjuk) - Anita Budi Rahayu (STKIP PGRI Nganjuk, 2021)
This study was conducted to identify the types of errors that made by the second year students of English Department of STKIP PGRI Nganjuk in their writing-I and to analyze what factor causes the students make errors in their writing. There are about 30 students who have taken the writing class. This qualitative study was conducted by document analysis and interview. The document analysis was done by collecting students' writing papers; it was taken from the lecturer who taught academic writing class. The paper became the primary source supported by related references as the secondary sources. The whole primary data were classified based on the types of errors, and then they were explained. The writer also used interview protocol to cross check the data got from document analysis. This was important technique to gather the information about the factor causes the students make errors in their academic writing. The research finding shows the type of error that the students often made many errors in tenses. These errors occurred due to their lack of understanding about tenses and their usage. The other minor errors are considered mistakes because they know the rules, especially in using capital, punctuation, and determiners. Based on the interview protocol, the errors were made because of the influence of the first language; the students often think in Indonesian then write in English. The process of transferring the language infected the errors. This also was influenced by the students' habit that seldom read the writing product after they write it. Actually, the errors can be revised if the students can pay much more attention to their writing product. From this evidence, the writer suggested that lectures teach and train their students in constructing sentences in many forms of tenses as prewriting activity. Other suggestion for the lectures is that they remind students about minor mistakes to prevent repeated mistakes. The lectures also have to plan valuable and effective feedback in order to enhance students' development in writing skill.